Field evaluation of the effects of a porcine circovirus type 2 vaccine on finishing pig growth performance, carcass characteristics, and mortality rate in a herd with a history of porcine circovirus-associated disease - Jacela, Jay Y.; Dritz, Steven S.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L. (My University, 2012)
Objective: To evaluate porcine circovirus type 2 (PCV2) vaccine influence on growth performance and mortality rate of finishing pigs. Materials and methods: The study treatments (vaccinated for PCV2 or nonvaccinated control and barrow or gilt) were arranged as a 2 × 2 factorial. Pigs (PIC L337 × 1050) were randomly assigned to Vaccinated or Control treatments within gender. In Experiment One, pigs were vaccinated at 9 and 11 weeks of age, and in Experiment Two, pigs were vaccinated at 5 and 7 weeks of age. Performance data were then collected during the finisher on-test period beginning when pigs were 11 weeks of age. Pig weights and feed intake were recorded on a pen basis. Results: In Experiment One, average daily gain (ADG), average daily feed intake, gain-to-feed ratio, and mortality were better (P < .05) in Vaccinated pigs than in Controls. In Experiment Two, there were vaccine-by-gender interactions for ADG (P < .01) and final weight (P < .05), as ADG was greater in Vaccinated barrows than in Vaccinated gilts (P < .01). Overall, greater ADG resulted in Vaccinated pigs being 2.9 kg heavier (P < .01) than Controls at market. Mortality rates of Vaccinated pigs were lower (P < .05) than those of Controls (2.8 percentage units in Experiments One and 6.2 percentage units in Experiment Two). Implications: The superior growth performance and lower mortality after vaccination confirmed the efficacy of the commercial PCV2 vaccine used in this study.
Keywords: Swine; Growth; Porcine circovirus type 2; Vaccine